Cranial imaging in children with malnutrition aged 6 to 60 months - Tiwari, Kavita; Goyal, Suresh; Soni, Ravi; Devaraj, Sunilkumar; Goyal, Saurabh; Gahlot, Kushal (International Journal of Contemporary Pediatrics, 2021)
Background: India has 57 million or more than a third of the world’s 146 million undernourished children. Protein energy malnutrition is associated with cerebral atrophy 2 which may be detrimental to intellectual development. The aim and objective of this stusy was to study the changes in the brain by cranial imaging in children with malnutrition aged 6 months to 5 years and to correlate these changes with severity of malnutrition. Methods: It was a hospital based prospective study done in Bal Chikitsalay, Maharana Bhupal government hospital, Udaipur during the study period July 2015 to July 2016. Total 120 children were enrolled, out of which 80 were severely malnourished, 20 were moderately malnourished and 20 normally nourished children undergoing neuroimaging for some other reason taken as controls. All the cases were subjected to CT scan and the following parameters were noted. Central atrophy was evaluated by bifrontal index (BFR) and bicaudate index (BCR). Cortical atrophy was evaluated by width of sylvian fissure (SFW) and widening of interhemispheric fissure (IHD). These parameters were then compared with the severity of malnutrition and among controls. Data was analysed with standard software of biostatics using parametric tests, Pearson’s correlation analysis, ANOVA test and student’s t test. Results: On an average 80% of SAM and 10% of MAM had various degree of cerebral atrophy while none of the controls showed significant degree of cerebral atrophy. Conclusions: Effect of malnutrition on brain can be objectively assessed by CT indices, BFR, BCR, SFW and IHD to define the degree of cerebral atrophy in the malnourished population.